Synthesis, Characterization and Copolymerization of N-(phenylamino)maleimide with MMA - B. L. Hiran; S. N. Paliwal; Jyoti Choudhary; P. R. Choudhary (E-Journal of Chemistry)
The free radical copolymerization of N-(phenylamino)maleimide (N-PAMI) was carried. The copolymerization with methyl methacrylate (MMA) was performed at 65°C with AIBN as the initiator in THF solvent. Resulting copolymer was characterized by density measurement, intrinsic viscosity, solubility, FT-IR & 1H NMR spectroscopy. Effect of the solvent and time on copolymer yield was also investigated. The molecular weight of copolymer was determined by gel permeation chromatography (GPC). The thermal stability of copolymer was determined by Thermogravimetric analysis (TGA).